5D BIM: an investigation into the integration of quantity surveyors within the BIM process. Issue 3 (12th February 2019) - Mayouf, Mohammad; Gerges, Michael; Cox, Sharon
Abstract : Purpose: This paper aims to investigate the integration of a quantity surveyor (QS) role and practice within the building information modelling (BIM) process to enable better implementation of five-dimensional building information modelling (5D BIM) (D is a result of the data/information dimension integrated in a BIM model). It proposes the use of a "level of development and level of detail" to provide a structured approach for QSs' integration within the BIM process for an improved implementation of 5D BIM. Design/methodology/approach: This paper uses semi-structured interviews with QSs from academic and industry in the UK. A total of 20 face-to-face semi-structured interviews were conducted with two groups (industrial and academic) of ten participants from the West Midlands region in the UK. The interview questions have focussed on gaining perspectives on BIM, BIM and government protocols for the QS profession, expectations and challenges when implementing 5D BIM. Findings: The findings show that BIM is perceived differently, and limitation of information obtained from the 3D models in BIM reduce the reliability of 5D BIM for QSs and implementing of 5D BIM needs an understanding of BIM workflow and information requirements. Research limitations/implications: Although the findings reveal many of the complexities that face QSs within the BIM process and the shortfalls of 5D BIM technology, the results may lack generalisation. Thus, future research seeks to test the proposed framework further. Practical implications: This paper elicits implications of shortfalls that impact the implementation of 5D BIM technology and the complexities that face QSs within the BIM process. Originality/value: This paper reveals the need to understand the process of integrating stakeholders and their information requirements for better implementation of technologies within BIM.